Molecular Coronary Plaque Imaging Using 18F-Fluoride. (August 2019) - Moss, Alastair J.; Doris, Mhairi K.; Andrews, Jack P.M.; Bing, Rong; Daghem, Marwa; van Beek, Edwin J. R.; Forsyth, Laura; Shah, Anoop S.V.; Williams, Michelle C.; Sellers, Stephanie; Leipsic, Jonathon; Dweck, Marc R.; et al.
Abstract : Background: Coronary 18 F-fluoride positron emission tomography identifies ruptured and high-risk atherosclerotic plaque. The optimal method to identify, to quantify, and to categorize increased coronary 18 F-fluoride uptake and determine its reproducibility has yet to be established. This study aimed to optimize the identification, quantification, categorization, and scan-rescan reproducibility of increased 18 F-fluoride activity in coronary atherosclerotic plaque. Methods: In a prospective observational study, patients with multi-vessel coronary artery disease underwent serial 18 F-fluoride positron emission tomography. Coronary 18 F-fluoride activity was visually assessed, quantified, and categorized with reference to maximal tissue to background ratios. Levels of agreement for both visual and quantitative methods were determined between scans and observers. Results: Thirty patients (90% male, 20 patients with stable coronary artery disease, and 10 with recent type 1 myocardial infarction) underwent paired serial positron emission tomography-coronary computed tomography angiography imaging within an interval of 12±5 days. A mean of 3.7±1.8 18 F-fluoride positive plaques per patient was identified after recent acute coronary syndrome, compared with 2.4±2.3 positive plaques per patient in stable coronary artery disease. The bias in agreement in maximum tissue to background ratio measurements in visually positive plaques was low between observers (mean difference, −0.01; 95% limits of agreement, −0.32 to 0.30) or between scans (mean difference, 0.06; 95% limits of agreement, −0.49 to 0.61). Good agreement in the categorization of focal 18 F-fluoride uptake was achieved using visual assessment alone (κ=0.66) and further improved at higher maximum tissue to background ratio values. Conclusions: Coronary 18 F-fluoride activity is a precise and reproducible metric in the coronary vasculature. The analytical performance of 18 F-fluoride is sufficient to assess the prognostic utility of this radiotracer as a noninvasive imaging biomarker of plaque vulnerability. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT02110303 and NCT02278211. Abstract : Supplemental Digital Content is available in the text.